1996
DOI: 10.1093/cercor/6.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Networks for Visual Reaching: Physiological and Anatomical Organization of Frontal and Parietal Lobe Arm Regions

Abstract: The functional and structural properties of the dorsolateral frontal lobe and posterior parietal proximal arm representations were studied in macaque monkeys. Physiological mapping of primary motor (MI), dorsal premotor (PMd), and posterior parietal (area 5) cortices was performed in behaving monkeys trained in an instructed-delay reaching task. The parietofrontal corticocortical connectivities of these same areas were subsequently examined anatomically by means of retrograde tracing techniques. Signal-, set-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
459
2
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 631 publications
(515 citation statements)
references
References 69 publications
46
459
2
1
Order By: Relevance
“…A large reciprocally connected neo-cortical network involving parietal (BA 7) and premotor areas (BA 6) is thought to be essential for planning and control of movements and anticipation of their consequences. This might explain the very similar time-courses of activity in these structures in the present study (Jeannerod, 1994;Johnson et al, 1996;Andersen et al, 1997).…”
Section: Functional Equivalence Of Overt and Covert Object Manipulationsupporting
confidence: 74%
“…A large reciprocally connected neo-cortical network involving parietal (BA 7) and premotor areas (BA 6) is thought to be essential for planning and control of movements and anticipation of their consequences. This might explain the very similar time-courses of activity in these structures in the present study (Jeannerod, 1994;Johnson et al, 1996;Andersen et al, 1997).…”
Section: Functional Equivalence Of Overt and Covert Object Manipulationsupporting
confidence: 74%
“…Recent anatomic work using retrograde virus transport has indicated that relatively few of the corticospinal neurons on the crown of the central sulcus have these direct projections (Rathelot and Strick 2009). There is also physiological evidence that, as one moves anterior from the central sulcus, the discharge of neurons may become less like that of muscles while taking on other higher-order characteristics (Johnson et al 1996;Kakei et al 2001). The multielectrode arrays that we used in this study preclude recording from within the bank of the central sulcus, and thereby may actually have missed many of these directly connected, musclelike neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies indicate that the discharge of many, but not all, M1 neurons is influenced by posture and external load. There is anatomic evidence that the proportion of neurons with these musclelike properties may increase with proximity to the central sulcus (Johnson et al 1996;Rathelot and Strick 2006). As such, M1 is now generally viewed as a heterogeneous structure, involved in the coding of both kinematics and kinetics, and perhaps also in the transformation of these commands (Kakei et al 2001;Kalaska et al 1989;Shen and Alexander 1997;Thach 1978).…”
mentioning
confidence: 99%
“…Sensory responses recorded in the premotor cortex in monkeys are related to the motor intention, implying a role in the preparation of voluntary movements (Boussaoud et al, 1995;Wise et al, 1997). These multimodal inputs to the premotor cortex come both from sensory association areas, and also from multisensory areas of the parietal lobe (Tanné-Gariépy et al, 2002;Johnson et al, 1996;Luppino et al 1999;Shipp et al, 1998). The latencies of the responses to sensory stimuli in the premotor cortex may be relatively short, which is compatible with direct access through the thalamus, for example, in agreement with recent anatomical studies (Morel et al, 2005;Cappe et al, 2009a) showing the existence of inputs from PuM directed towards PMd and PMv.…”
Section: Role Of the Pulvinarmentioning
confidence: 99%